The Problem of Personnel in the Cinema and Theater Fields: The System of Training Personnel with Secondary Specialty and Higher Education - Ochilova Kamola (Genius Journals, 2023)
This article deals with the issue of personnel in the field of cinema and theater: the system of training personnel with secondary and higher education. Based on scientific data, the author studied and analyzed the specific aspects of teaching history in higher education institutions based on the available literature.
Keywords: Cinema; theater; personnel issue; personnel with secondary special